2000
DOI: 10.1021/la0005208
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy Study of Immobilization Processes for Heavy Metals in Calcium Silicate Hydrates: 1. Case of Lead

Abstract: Trace amounts of heavy metals can be detected in cement. The major source is due to heavy metals naturally present in some of the raw materials used for clinkers manufacture. One way to predict the long-term behavior of these metals is to know which types of links occur between heavy metals and major elements (Ca, Si, Al, Fe). Since tricalcium silicate (C3S) is the major phase of cement-base material, a XAS study at the Pb-LIII edge has been carried out to elucidate the binding mechanisms of Pb by calcium sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 30 publications
2
34
0
2
Order By: Relevance
“…Therefore, As, Pb, and most likely Cu are expected to be partially encapsulated in pozzolanic products or incorporated into stable phases at low pH. Moreover, Pb is reported to be sequestered into Pb-Si-O compounds at high alkaline pH values (Rose et al 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, As, Pb, and most likely Cu are expected to be partially encapsulated in pozzolanic products or incorporated into stable phases at low pH. Moreover, Pb is reported to be sequestered into Pb-Si-O compounds at high alkaline pH values (Rose et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, lead silicates are also possible compounds responsible for Pb immobilization. Rose et al (2000) reported that Pb could be incorporated within the CSH structure through linkages to Si-O chains upon hydration of tricalcium silicate, which is the main compound in Portland cement. Lead silicate (Pb 3 SiO 5 ) has been reported as the compound responsible for Pb immobilization when the fly ash was used on Pb contamination at 3.125 %.…”
Section: Sem-edx Analysesmentioning
confidence: 99%
“…The application of XAS to complex matrices in relation to environmental fate and behavior of contaminants is still relatively rare, but it has been employed in a limited number of studies of the speciation of metals in cement pastes, including chromium [9], cobalt [10], copper [11], lead [12], neodymium [13], selenium [14], tin [15], uranium [16] and zinc [17], as well as nickel [18][19][20]. Apart from Rinehart et al [9], who examined the oxidation state of chromium in a s/s contaminated soil and showed that this was not affected by S/S, and Hsaio et al [11], who indicated that S/S respeciated CuCl2 and reduced forms of copper in municipal waste incinerator air pollution control residues to Cu(OH)2, other studies have all prepared hydrated cement pastes by mixing pure solutions of soluble metal salts with cement powder.…”
Section: Introductionmentioning
confidence: 99%
“…Although X-ray absorption fine structure (XAFS) spectroscopy has become an increasingly important tool for investigating immobilization processes in cementitious systems (e.g., [14][15][16][17][18][19][20][21][22][23][24][25][26]), very few studies have used XAFS to develop a molecular-level understanding of the U(VI) uptake by cementitious materials [27,28]. In these studies the coordination environment of U(VI)-doped untreated and hydrothermally treated concrete was probed in the alkaline pH range (pH 9-12).…”
Section: Introductionmentioning
confidence: 99%